2018
DOI: 10.1139/bcb-2018-0073
|View full text |Cite
|
Sign up to set email alerts
|

The phosphoinositide 3-kinase pathway and glycogen synthase kinase-3 positively regulate the activity of metal-responsive transcription factor-1 in response to zinc ions

Abstract: Metal-responsive transcription factor-1 (MTF-1) is a metal-regulatory transcription factor essential for induction of the genes encoding metallothioneins (MTs) in response to transition metal ions. Activation of MTF-1 is dependent on the interaction of zinc with the zinc fingers of the protein. In addition, phosphorylation is essential for MTF-1 transactivation. We previously showed that inhibition of phosphoinositide 3-kinase (PI3K) abrogated Mt expression and metal-induced MTF-1 activation in human hepatocel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 68 publications
1
4
0
1
Order By: Relevance
“…In this work, we found that in myoblasts differentiated in the absence of insulin, the expression of MTF1 was decreased. This evidence points to a potential regulation of MTF1 expression and phosphorylation mediated by PI3K, and possibly other kinases, in the skeletal muscle lineage, which is in agreement with previous studies (78). Whether the activation of these kinases is regulated by Cu or Zn in the skeletal muscle lineage remains to be elucidated.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this work, we found that in myoblasts differentiated in the absence of insulin, the expression of MTF1 was decreased. This evidence points to a potential regulation of MTF1 expression and phosphorylation mediated by PI3K, and possibly other kinases, in the skeletal muscle lineage, which is in agreement with previous studies (78). Whether the activation of these kinases is regulated by Cu or Zn in the skeletal muscle lineage remains to be elucidated.…”
Section: Discussionsupporting
confidence: 93%
“…MTF1 transcriptional activity is associated with the availability of Zn ions (73); however, the molecular mechanisms by which metals activate MTF1 remain unclear. Current models for MTF1 activation include: 1) stimulation by free cytosolic Zn; 2) interaction with Zn released from metallothioneins (MTs); or 3) MTF1 phosphorylation/dephosphorylation (72,(74)(75)(76)(77)(78). Under normal conditions, MTF1 is primarily located in the cytoplasm.…”
mentioning
confidence: 99%
“…PI3K-Akt signaling pathway negatively modulates LPS-induced acute inflammatory responses. Factually, its inhibition enhances the activation of NF-κB, AP-1, and Egr-1 transcription factors as well as expression of TNF-α, IL-6 and tissue factor in human monocytic cells (Huang et al, 2011), which results in impaired immune responses and reduced susceptibility to autoimmune and inflammation (Andeol et al, 2018). This pathway is also involved in the regulation of autophagy in immune response, so as to remove bacteria from gastrointestinal infections.…”
Section: Resultsmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) is a group of endopeptidases that can degrade extracellular matrix protein in tumour microenvironment [37], thereby causing tumour cells to lose their connection to the basement membrane [38]. The PI3K/Akt/m TOR signalling pathway is a very important pathway in the cell signalling pathway [39,40]. PI3K signalling disorders are closely related to the occurrence and development of malignant tumours, and affect the formation of VM channels [41].…”
Section: Discussionmentioning
confidence: 99%